2020
DOI: 10.34172/ijep.2020.04
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Antibiotic Susceptibility of Pseudomonas aeruginosa and Acinetobacter baumannii Infections in Pediatrics Intensive Care Unit of Imam Ali Hospital, Karaj, Iran During 2017- 2018

Abstract: Background: Pseudomonas aeruginosa and Acinetobacter baumannii are widely ubiquitous in nature. In addition, they are opportunistic pathogens for humans and the common cause of nosocomial infections. Objective: Due to the increased antibiotic resistance in the treatment of nosocomial infections, this study aimed to evaluate the antibiotic susceptibility pattern of P. aeruginosa and A. baumannii in the pediatrics intensive care unit (PICU). Materials and Methods: Totally, 280 clinical samples from PIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…In this study, the isolated strains from patients hospitalized in the ICU demonstrated resistance to a broad spectrum of antibiotics. This observation aligns with previous studies that have reported the high resistance of A. baumannii isolates to various antimicrobial agents in neurosurgical and neonatal ICUs (40)(41)(42). Efflux pumps, such as adeA and adeS, are recognized as significant mechanisms of resistance in A. baumannii, as they actively expel toxic substances, including antibiotics, from the bacterial cell (43).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the isolated strains from patients hospitalized in the ICU demonstrated resistance to a broad spectrum of antibiotics. This observation aligns with previous studies that have reported the high resistance of A. baumannii isolates to various antimicrobial agents in neurosurgical and neonatal ICUs (40)(41)(42). Efflux pumps, such as adeA and adeS, are recognized as significant mechanisms of resistance in A. baumannii, as they actively expel toxic substances, including antibiotics, from the bacterial cell (43).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, of the 66 clinical A. baumannii isolates evaluated, 1.5 % were qualified as PDR, 72.7 % were designed as XDR and 16.7 %, were qualified as MDR, whereas, 85.6 % of A. baumannii isolates were designed as MDR, and 14.4% were qualified as XDR about 31 . The resistance phenotype of Gram negative bacteria in urine is diverse, among all isolates in urine 35, 62.8 % were qualified as MDR, and 28.5 % were qualified as XDR.…”
Section: Discussionmentioning
confidence: 99%